2018
DOI: 10.3389/fimmu.2018.01123
|View full text |Cite
|
Sign up to set email alerts
|

The C-Type Lectin Receptor DC-SIGN Has an Anti-Inflammatory Role in Human M(IL-4) Macrophages in Response to Mycobacterium tuberculosis

Abstract: DC-SIGN (CD209/CLEC4L) is a C-type lectin receptor (CLR) that serves as a reliable cell-surface marker of interleukin 4 (IL-4)-activated human macrophages [M(IL-4)], which historically represent the most studied subset within the M2 spectrum of macrophage activation. Although DC-SIGN plays important roles in Mycobacterium tuberculosis (Mtb) interactions with dendritic cells, its contribution to the Mtb–macrophage interaction remains poorly understood. Since high levels of IL-4 are correlated with tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 57 publications
0
43
1
2
Order By: Relevance
“…The siRNA gene silencing in BV2 cells was performed as previously described [32]. Briefly, BV2 cells were seeded into a 6-well plate (Corning Inc.) at a density of 1.5 × 10 5 cells/well 24 h prior to transfection.…”
Section: Rna Interference Experimentsmentioning
confidence: 99%
“…The siRNA gene silencing in BV2 cells was performed as previously described [32]. Briefly, BV2 cells were seeded into a 6-well plate (Corning Inc.) at a density of 1.5 × 10 5 cells/well 24 h prior to transfection.…”
Section: Rna Interference Experimentsmentioning
confidence: 99%
“…18 A recent report showed that silencing DC-SIGN on IL-4treated human monocyte-derived macrophages enhances M. tuberculosis-induced pro-inflammatory cytokine production. 19 These findings showed that DC-SIGN expression on myeloid cells affects the pathogenesis of mycobacterial infection. However, how the expression of DC-SIGN in non-immune cells impacts the pathogenic mechanism of an infection has never been investigated.…”
Section: Introductionmentioning
confidence: 90%
“…В отсутствие этого белка IL-4-активированные макрофаги проявляли провоспалительный фенотип при заражении M. tuberculosis и приобретали лучшую способность контролировать внутриклеточный рост этого патогена. Однако в отсутствие DC-SIGN при туберкулезной инфекции отмечалось снижение восстановления и ремоделирования тканей -процессов, являющихся характерными функциональными проявлениями деятельности альтернативно активированных макрофагов [61].…”
Section: Dc-signunclassified